FARMERS PREFERENCES IN THE USE OF NEW SUPERIOR VARIETY OF RICE (Oryza sativa L.) SEEDS IN RAJAPOLAH DISTRICT, TASIKMALAYA REGENCY, WEST JAVA PROVINCE: PREFERENSI PETANI DALAM PENGGUNAAN BENIH VARIETAS UNGGUL BARU TANAMAN PADI (Oryza sativa L.) DI KECAMATAN RAJAPOLAH KABUPATEN TASIKMALAYA PROVINSI JAWA BARAT - Rani Ratnasari; Achdiyat (Jurnal Penyuluhan Pertanian, 2022)
This study aims to describe farmers' preferences in the use of new superior varieties of rice seeds and analyze the factors that influence farmers' preferences. This research was conducted in Rajapolah District, Tasikmalaya Regency. The data analysis of this study used descriptive and Chi-square analysis techniques. Farmers' preferences are known based on scores. Primary data was generated from filling out a questionnaire by 74 respondents. Characteristics of farmers consist of: age, formal education, experience in farming, knowledge of farmers. External factors: the role of extension workers, extension activities and the availability of facilities and infrastructure. The dependent variable consists of attributes, experience and satisfaction. The results of this study indicate that farmers' preferences reach the high criteria (18.92%) and are dominated by the medium criteria (79.73%). Based on seed attributes, farmers in Rajapolah District tend to prefer the Inpari 32 variety to the Mekongga variety, taking into account the attributes based on pest resistance. Experience and satisfaction with the Inpari 32 variety showed superior production even though the taste of rice was preferred by the Mekongga variety. Factors that influence farmers' preferences are indicators of knowledge on attribute indicators, age on experience, knowledge on experience, availability of facilities and infrastructure on experience and availability of facilities and infrastructure on satisfaction.